The Effect of Cone Drill Training on the Agility of Football Athletes at Cibubur Youth Athlete Training Center (CYATC) - Eko Wahyono; Zulfikar H. Wada; Zeth Boroh (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Agility is an important component of physical fitness in football as it supports athletes’ ability to change direction quickly, accurately, and with balance. Adolescent football players require optimal agility to enhance their technical and tactical performance. This study aimed to determine the effect of cone drill training on the agility of football athletes at Cibubur Youth Athlete Training Center in 2025. The research employed an experimental method using a pretest–posttest control group design. The sample consisted of football athletes from Cibubur Youth Athlete Training Center who received cone drill training as the intervention. Agility was measured before and after the intervention using the Arrowhead Agility Test. Data were analyzed using a paired sample t-test. The results showed an improvement in agility, indicated by a reduction in Arrowhead Agility Test completion time in the group that received cone drill training. Statistical analysis revealed a significant difference between pretest and posttest scores (p < 0.05). In conclusion, cone drill training has a significant effect on improving agility in adolescent football athletes and can be considered an effective training method within athlete development programs.